Countryside and folk culture in central Poland (empirical study) (Sociology of rural worlds in Poland and France: field research and studies, 2024)
The text is dedicated to folk culture in the regions of Sieradz and Piotrków Trybunalski, located in central Poland. It presents an empirical research study on lifestyles, customs, art and their intergenerational transmission in multigenerational families through the cultural system I – the familial one and II – local institutions (ethnographic museums, schools).